Fleet Management System - Yong, Hee Chong (2001)

(untitled)
Managing paper-driven employee travel and expenses is a slow, fragmented process with abundant potential for uncontrolled spending. As a result, there is a need for a Travel and Expenses Management System to provide a better control and reduce the cycle time. Customizing a standard software package to suit the company operation is selected in order to ensure that the company can leverage from the industry proven best practices of travel and expenses claim processes and at the same time maintain the company unique requirements. This report describes the needs for expense claim automation and the process to customize a standard Travel and Expenses Management System package. The project covers the use of Microsoft Solution Framework (MSF) process model, functional decomposition, process flow diagram and program flow diagram to represent the current system and the proposed system. This paper introduces a web-based Travel and Expenses Management System to enhance the expense claim processes. The system analysis outlines the system requirements by going through the functionality assessment, option assessment and gap resolution. The functional specification illustrates the customization needed by focusing on functionality, technical review, input, processing and output. In addition, the paper shows the fit of MSF process model in this project development and proposes the use of MSF team model for the project involving team efforts. It also outlines the possible additional features and functionalities that could further improve the system.